Konsep Hak Milik Dalam Al-Qur’an Sebagai Kerangka Etika Ekonomi Islam: Analisis Tafsir Tematik Terhadap Distribusi Kekayaan, Serta Larangan Penumpukan Harta Dan Tanggung Jawab Sosial - Adryan Irawan; Achmad Abubakar; Sohrah Sohrah (Sharing: Journal of Islamic Economics Management and Business, 2026)
This study aims to reveal and analyze the concept of ownership in the Qur'an from the perspective of thematic interpretation (tafsir maudhu'i) in order to construct a comprehensive framework of Islamic economic ethics, particularly in the aspects of wealth distribution, the prohibition of wealth accumulation, and social responsibility as a normative solution to the problem of economic inequality faced by contemporary Muslims. This research employs a qualitative approach based on library research using the thematic tafsir method (maudhu'i), integrating a linguistic (lughawi) interpretative approach to analyze the meanings of Qur'anic terms related to ownership and wealth distribution, in order to uncover the normative implications of these verses in shaping an Islamic economic ethical framework that includes the prohibition of wealth hoarding and the obligation of social responsibility. The findings indicate that the Qur'an systematically constructs a holistic framework of Islamic economic ethics through the concept of ownership as a trust (amanah) entrusted by Allah, the obligation of wealth distribution, the prohibition of wealth accumulation, and social responsibility, all of which are interconnected as an inseparable normative unity. Thus, it is expected that the Qur'anic concept of ownership can serve as an academic and policy foundation for the development of contemporary Islamic economic systems, particularly in formulating regulations on zakat, waqf, and Islamic financial instruments that are more just and oriented toward the overall welfare (maslahah) of the ummah.